Implementation of guppy fish (Poecilia reticulata), and a novel larvicide (Pyriproxyfen) product (Sumilarv 2MR) for dengue control in Cambodia: A qualitative study of acceptability, sustainability and community engagement. - Muhammad Shafique; Sergio Lopes; Dyna Doum; Vanney Keo; Ly Sokha; BunLeng Sam; Chan Vibol; Neal Alexander; John Bradley; Marco Liverani; Jeffrey Hii; Leang Rithea; et al. (Public Library of Science (PLoS), 2019)
Background In Cambodia dengue vector control activities are focused on larviciding with temephos and pyrethroid based adulticide sprays to which Aedes have been shown to be increasingly resistant. A cluster randomized trial assessed the impact of using biological control tools (guppy fish, pyriproxyfen (PPF), and Communication for Behavioral Impact (COMBI) activities in combination), which would be used in a value comparison to traditional chemical control tools. Given these new intervention methods, a qualitative assessment was designed in order to represent the quality of understanding, acceptance, and implementation by participants. Methodology/principal findings A total of 103 participants in 12 Focus Group Discussions (FGDs) and nine In-Depth Interviews (IDIs) were included in the study. The majority of participants in intervention villages (50 out of 80) preferred guppy fish over other vector control methods due to ease of use and rearing, quick reproduction and propensity to eat larvae. A substantial number of participants (11 out of 40) in intervention villages with PPF favored it due to long-lasting effectiveness, lack of smell and easy maintenance. Participants showed high demand for both interventions and were willing to pay between 100-500 riel (0.03-0.13 USD). Nearly all participants perceived that the interventions resulted in a reduction in Aedes mosquitos (both adults and immatures) and dengue cases. The presence of larvae in the water despite the use of PPF was a source of concern for some participants, although this was overcome in some cases with proper health education through health volunteers. Interpersonal communication through health volunteers was the most favorite method of transmitting prevention messages. Conclusions/significance The community led COMBI strategy resulted in high acceptance and perceived effectiveness of the interventions in target villages. Health volunteers are an effective and accepted channel of communication to engage communities, disseminate information and promote behavioral change at the household and community level. If shown effective through corresponding entomological surveys, the interventions should be continued and further strengthened to ensure they are accessible, available and affordable.